Islamic Educational Philosophy in The Testament of New Experience Reflection by TGKH. Muhammad Zainuddin Abdul Madjid - Tabibuddin, M.; Thohri, Muhammad; Wathoni, Lalu Muhammad Nurul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This research aims to explore and analyze the concepts of Islamic educational philosophy contained in the work